The Profile of Antihypertensive Drug Prescriptions and Interactions at Pindad General Hospital - Yane S. Herliany; Siti R. Wahyuningsih (Universitas Padjadjaran, Indonesia)
Hypertension is a major problem in the world. World Health Organization (WHO) reported that 1.13 billion people in the world suffer from hypertension. This study aimed to determine antihypertensive prescription profile and drug interaction in outpatient installation at PINDAD General Hospital, Bandung in January 2019. This study was non-experimental observational studies with retrospective data collection. There were 381 patients with hypertension (50,13% female and 49,87% male). The most widely used antihypertensive drug is Amlodipine (33,28%) and Calcium Channel Blocker drug (34,20%). Moreover, we found 74,07% was moderate drug-drug interaction (DDI) with Amlodipine and Lisinopril as the most common cases (21,08%). We concluded that 15,7% prescription contain antihypertensive drugs and moderate DDI occurred in the use of amlodipine and lisinopril. DDI should get more attention due to the clinical manifestations that may occur in patients.